Naphthalene diimides with improved solubility for visible light photoredox catalysis - Reiß, Barbara; Wagenknecht, Hans-Achim (Beilstein Journal of Organic Chemistry, 2019)
Five core-substituted naphthalene diimides bearing two dialkylamino groups were synthesized as potential visible light photoredox catalysts and characterized by methods of optical spectroscopy and electrochemistry in comparison with one unsubstituted naphthalene diimide as reference. The core-substituted naphthalene diimides differ by the alkyl groups at the imide nitrogens and at the nitrogens of the two substituents at the core in order to enhance their solubility in DMF and thereby enhance their photoredox catalytic potential. The 1-ethylpropyl group as rather short and branched alkyl substituent at the imide nitrogen and the n-propyl group as short and unbranched one at the core amines yielded the best solubilities. The electron-donating diaminoalkyl substituents together with the electron-deficient aromatic core of the naphthalene diimides increase the charge-transfer character of their photoexcited states and thus shift their absorption into the visible light (500–650 nm). The excited state reduction potential was estimated to be approximately +1.0 V (vs SCE) which is sufficient to photocatalyze typical organic reactions. The photoredox catalytic activity in the visible light range was tested by the α-alkylation of 1-octanal as benchmark reaction. Irradiations were performed with LEDs in the visible light range between 520 nm and 640 nm. The irradiation by visible light together with the use of an organic dye instead of a transition metal complex as photoredox catalyst improve the sustainability and make photoredox catalysis “greener”.
Keywords: chromophore; dyes; electrochemistry; photochemistry; photoredox catalysis